Factors Affecting the Working Hours of the Elderly in the Agricultural Sector in Buduk Village, Mengwi District - Ni Luh Gede Dyana Pandu Widjayanti; Anak Agung Istri Ngurah Marhaeni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The objectives of this study are: (1) to analyze the motivation of elderly individuals to remain employed in the agricultural sector; (2) to examine the simultaneous and partial effects of elderly health, work experience, age, and income outside the agricultural sector on the working hours of the elderly in agriculture; and (3) to analyze the moderating role of income outside the agricultural sector in the relationship between elderly health and the working hours of elderly individuals in the agricultural sector in Buduk Village, Mengwi District. This study employed a quantitative, associative approach conducted in Buduk Village, with a sample size of 100 elderly individuals aged 60 and above. The sampling method used was non-probability sampling, including accidental sampling, snowball sampling, and purposive sampling techniques. Data were collected through observation, structured interviews, and in-depth interviews. The data were analyzed using moderation regression analysis and processed with the assistance of SPSS software. The results of the study indicate that: (1) the primary motivation for elderly individuals to continue working is the absence of others to manage their agricultural land; (2) the variables of elderly health, work experience, and income outside the agricultural sector have a negative and significant effect on the working hours of the elderly in agriculture, while the age variable has a negative but insignificant effect; (3) income outside the agricultural sector serves as a pseudo-moderating variable in the relationship between elderly health and their working hours in the agricultural sector in Buduk Village. The implications of these findings highlight the need for policies that support improving the quality of life of the elderly and empowering them economically through alternative income sources that do not rely heavily on physical labor.